2015
DOI: 10.1002/jwmg.961
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of an immunocontraceptive vaccine on eastern fox squirrels

Abstract: Managing pest species in urban and suburban areas is challenging, and contraception may provide a socially acceptable and effective management option for many species. The immunocontraceptive vaccine, GonaCon, effectively inhibits reproduction in many species of wildlife, but the behavioral effects are not yet well understood. Contraceptive-induced changes in behavior could raise animal welfare concerns and alter survival and reproductive rates in populations. These vital rates frequently are incorporated in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…2011) but no effects were observed on time‐activity budgets, dominance, and aggression in eastern fox squirrels ( Sciurus niger ) treated with GonaCon TM (Krause et al. 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2011) but no effects were observed on time‐activity budgets, dominance, and aggression in eastern fox squirrels ( Sciurus niger ) treated with GonaCon TM (Krause et al. 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Among side effects of contraceptives in rodent species, injection site abscesses were found in eastern gray squirrels (Sciurus carolinensis) injected with GonaCon TM (Pai et al 2011) but no effects were observed on time-activity budgets, dominance, and aggression in eastern fox squirrels (Sciurus niger) treated with GonaCon TM (Krause et al 2015).…”
Section: Yesmentioning
confidence: 99%
“…These differences were commensurate with the higher metabolic demands of pregnancy and lactation. Conversely, GonaCon did not affect social and spatial behaviour in Eastern fox squirrels (Sciurus niger (Krause et al 2015)) and in wild boar (Massei Fig. 13 Variation in mean (± SE) body weight (kg) for males in the vaccinated and control groups.…”
Section: Discussionmentioning
confidence: 97%
“…For example, GonaCon administration in dogs can cause swelling and muscular atrophy at the injection site [ 32 ], as well as chronic granulomatous myositis and diffuse coagulative necrosis 33. GonaCon has been documented in a variety of species, and minor to severe side effects were reported in horses ( Equus caballus ), eastern fox squirrels, and non-human primates [ 58 , 59 ]. In the present study, we emulsified a multimer construct protein with an equal volume of MONTANIDE ISA 206 VG adjuvant.…”
Section: Discussionmentioning
confidence: 99%